1991
DOI: 10.1007/bf01886508
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lactation products on the temporal expression of histo-blood group antigens in the intestines of suckling pigs: lectin histochemical and immunohistochemical analysis

Abstract: Lectins and carbohydrate-specific monoclonal antibodies were used as cytochemical probes to investigate the possible influence of lactation products on the expression of intestinal membrane and secretory glycoconjugates in suckling piglets. Two different lactational regimes were compared; the first involved normal rearing of piglets for 8 weeks on a single dam and the second involved repeated cross-fostering of littermates onto recently farrowed sows, thereby restricting them to early milk. Five histo-blood gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…Evidently, the ingestion of colostral pro teins in the first 24 h promoted an initial and rapid decline in lactase but did not induce longer term precocious changes in this en zyme or in membrane glycosylation. This sug gests that sustained exposure to colostrum/ early milk is necessary to fully entrain the more marked effect on lactase and glycosyla tion we previously reported [10,28], This contrasts with the effect on sucrase where fol lowing postnatal colostrum ingestion, en hanced activity of the enzyme was sustained throughout the experimental period.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Evidently, the ingestion of colostral pro teins in the first 24 h promoted an initial and rapid decline in lactase but did not induce longer term precocious changes in this en zyme or in membrane glycosylation. This sug gests that sustained exposure to colostrum/ early milk is necessary to fully entrain the more marked effect on lactase and glycosyla tion we previously reported [10,28], This contrasts with the effect on sucrase where fol lowing postnatal colostrum ingestion, en hanced activity of the enzyme was sustained throughout the experimental period.…”
Section: Discussioncontrasting
confidence: 50%
“…In our pre vious investigations we observed that both the normal postnatal decline in lactase activity, and the fucosylation of microvillar glycoconjugates were precociously enhanced when piglets ingested early lactation milk [ 10,20,28]. In the present study the marked decrease in lactase activity in CF pigs occurred at week 1 post parturn, well before membrane fucosylation was detected in the cytochemical assays.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This indicates that other lactobacilli than L. plantarum were present. The presence of these lactobacilli can be due to changes in the available substrates or products (14,18) or alterations in the intestine, e.g., diet-induced intestinal glycosylation (12) or epithelial proliferation by VFA (27). The influence of L. plantarum on Enterobacteriaceae in the GIT is difficult to explain from the results of this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Both FUT1 and FUT2 contribute to formation of α1,2-fucosylated antigenic structures 40 as determinants of pig erythrocyte blood groups, whose full expression was evident at 5-8 weeks of life. [42][43][44] Binding specificity of AAL with AAL-Sepharose column 45 and crystal structure of the complex between AAL and fucose 46 showed that this lectin recognizes not only α1,6-core fucosylated N-linked glycoproteins but also α1,2-, α1,3-, and α1,4-fucosylated residues. The broader range of fucose potential binding sites of AAL indicates that also some mucin O-glycans, important for adhesion, cell signaling, and defining various blood group epitopes, react with AAL.…”
Section: Fucosylationmentioning
confidence: 99%